Cytotoxic effect of phoenix dactylifera L. (ajwa date extract) on oral squamous cell carcinoma cell line - Shahbaz, Khushboo (2020)
Oral squamous cell carcinoma (OSCC) is a major public health problem globally. The prognosis for patients with OSCC remains poor despite the advancement in treatment modalities and diagnostic technology. Therefore, there is an urgent need to explore natural products that effectively cure this disease. Ajwa date fruit, was reported to have strong anti-oxidant and anti-cancer properties. However, no study has focused on Ajwa date flesh and pits extract effect on OSCC yet. The aim of the current study is to investigate the cytotoxic and apoptotic potential of Ajwa date flesh (ADF) and Ajwa date pit (ADP) extract on HSC-2 cell line. ADF and ADP were extracted with solvent extraction method using hexane, acetone and ethanol, which were then subjected to antioxidant assay by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 3-(4,5- Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) assay for cytotoxicity assessment. For apoptosis assessment, Annexin-V apoptosis detection kit for 24, 48 and 72 hours was used. In this study, acetone extracts of ADF and ADP had the highest radical scavenging and antioxidant activities followed by the ethanolic extracts. Whereas, ADP appeared to have significantly higher antioxidant effects than the ADF. In this study, the MTT assay demonstrated that acetone extracts of ADF and ADP were significantly cytotoxic against HSC-2 cells in a dose and time-dependent manner. The half inhibitory concentration (IC50) of ADF was found to be 8.69 mg/ml at 24h and the maximum cell growth inhibition was observed at 50 mg/ml. The IC50 for the ADP was found to be 0.97 mg/ml at 24h and the maximum cell growth inhibition was observed at 5 mg/ml. Statistical analysis of the flowcytometry assay showed that the treatment with ADF and ADP extracts had significant apoptotic effect which occurred in a dose-dependent manner. At treatment with higher doses of ADP and ADF extract HSC-2 cells were seen in late apoptotic stage. ADP extract demonstrated higher apoptotic activity than ADF extract. In addition, combined treatment of ADF and ADP were also performed on HSC-2 cells which demonstrated higher apoptotic activity when compared to the single extract. In conclusion, Ajwa date fruit has promising cytotoxic effect by inhibiting growth and proliferation of OSCC cells and inducing cell death by apoptosis. Furthermore, high radical scavenging activity of ADP will promote it as a potential candidate for further research to isolate the antioxidant compounds and to be used in combination with the fruit flesh in the development of anti-cancer drug in future.